The Influence of IT Literacy on Lecturer performance - Birru Muqdamien; Ilzamuddin Makmur; Nafan Tarihoran (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
One of the factors that influence the success of an organization's business is the management of information technology (IT) infrastructure that is run well, the Information Technology Literacy as a provider of IS/IT products and services must have the ability to do so. This research consists of two types of research, namely correlation research which will examine the relationship between internal customer satisfaction and seven independent variables. Results of correlation analysis showed that there was a significant effect positive between internal customer satisfaction with seven variable quality of the products and services of IS/IT (reject H 0 hypothesis 1) and there is significant influence positively the quality of the products and services of IS / IT to the perception of improved performance internal customers (reject H 0 in hypothesis 2). The average value of the satisfaction dependent variable is 3.326 and the dependent variable is the perception of increased internal customer performance: 3,430 which means that internal customers currently feel quite satisfied and feel a sufficient increase in their performance after receiving and using the IS/IT products and services provided. by the Information System Service Bureau at STT-PLN . The results of the Mann-Whitney analysis reject H 0 in hypothesis 3, in other words there are significant differences in the assessment of performance aspects between internal customers and IT personnel on the performance of the IT Literacy. Aspects that include: response to problems, development of IS and viruses.